Understanding of Labor Crimes for Indonesian Migrant Workers (PMI) (Study on the Implementation of Law Number 18 Year 2017 on the Protection of Indonesian Migrant Workers) - Dewi, Aida; Anang Setiyana (Widya Pranata Hukum : Jurnal Kajian dan Penelitian Hukum, 2024)
Law No. 18/2017 on the Protection of Indonesian Migrant Workers (referred to as PPMI Law) is the legal basis for the protection of Indonesian migrant workers. The passing of this law marks the end of a long slow and steep journey of the legislative process for the protection of Indonesian migrant workers who face vulnerability at every turn, ranging from wage evictions, persecution, sexual harassment, rape and even the death penalty. The spirit of Law No. 18/2017 as outlined in its explanation is to protect migrant workers from human trafficking, including slavery and forced labor, victims of violence, arbitrariness, crimes against human dignity, and other treatment that violates human rights. Despite contributing to the country's remittances, many PMIs experience various actions that violate their rights while working abroad. that there are PMIs are vulnerable to rights violations or unlawful acts committed by employers or other parties. The method used is normative method or normative juridical approach. Where to sharpen the research analysis, the author uses a case approach and a statutory approach and a sociological approach. The stages carried out in researching patterns of community behavior are combined with literature so that it will be found that things should be done or accepted in balance with their application / practice and the final stage analyzes the Understanding of Employment Crimes for PMI (Indonesian Migrant Workers) (Study on the Application of Law Number 18 of 2017 concerning the Protection of Indonesian Migrant Workers). Based on data from the Crisis Center of the Indonesian Migrant Workers Protection Agency (BP2MI) in 2022, some of the problems faced during 2019-2021 included unpaid salaries, PMI failing to depart, trafficking, work not in accordance with the work agreement, acts of violence from employers, depression / mental illness, fraudulent employment opportunities, and so on.